Mitigating strategies and nursing response for cancer care management during the COVID‐19 pandemic: an Italian experience. (2nd October 2020) - Zeneli, A.; Altini, M.; Bragagni, M.; Gentili, N.; Prati, S.; Golinucci, M.; Rustignoli, M.; Montalti, S.
Abstract : Aim: To describe our response to the COVID‐19 emergency in a cancer centre to enable other nursing organizations to determine which elements could be useful to manage a surge of patients in their own setting. Background: The COVID‐19 pandemic represents one of the most challenging healthcare scenarios faced to date. Managing cancer care in such a complex situation requires a coordinated emergency action plan to guarantee the continuity of cancer treatments for patients by providing healthcare procedures for patients, caregivers and healthcare professionals in a safe environment. Procedures: We describe the main strategies and role of nurses in implementating such procedures. Results: Nurses at our hospital were actively involved in COVID‐19 response defined by the emergency action plan that positively contributed to correct social distancing and to the prevention of the spread of the virus. Implications for nursing and health policies: Lessons learned from the response to phase I of COVID‐19 have several implications for future nursing and health policies in which nurses play an active role through their involvement in the frontline of such events. Key policies include a coordinated emergency action plan permitting duty of care within the context of a pandemic, and care pathway revision. This requires the rapid implementation of strategies and policies for a nursing response to the new care scenarios: personnel redistribution, nursing workflow revision, acquisition of new skills and knowledge, effective communication strategies, infection control policies, risk assessment and surveillance programmes, and continuous supplying of personal protective equipment. Finally, within a pandemic context, clear nursing policies reinforcing the role of nurses as patient and caregiver educators are needed to promote infection prevention behaviour in the general population.